2020
DOI: 10.1177/1524838019899486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Family Violence Exposure on Adolescent Academic Achievement: A Systematic Review

Abstract: Millions of children are exposed to family violence around the world; however, the effects on adolescent academic achievement are poorly understood. Using a systematic search and review methodology, we synthesized studies that quantitatively examined the effects of exposure to family violence on academic achievement among adolescents. We searched for peer-reviewed, English-language articles in nine online databases. Thirteen studies that examined adolescents were included, where family violence exposure was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…As a result, a systematic review of young adult romantic relationship outcomes is essential. Previous systematic reviews have focused on IPC mainly with children (Fong et al, 2019; van Eldik et al, 2020; Zemp et al, 2016), adolescents (Supol et al, 2020), and physical health outcomes in adults (Bair-Merritt et al, 2006). Even though attention has been given to relationship outcomes in young adults, research has been limited to the perpetration of IPV in young adults’ relationships (Kimber et al, 2018), and perpetration by black men (Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a systematic review of young adult romantic relationship outcomes is essential. Previous systematic reviews have focused on IPC mainly with children (Fong et al, 2019; van Eldik et al, 2020; Zemp et al, 2016), adolescents (Supol et al, 2020), and physical health outcomes in adults (Bair-Merritt et al, 2006). Even though attention has been given to relationship outcomes in young adults, research has been limited to the perpetration of IPV in young adults’ relationships (Kimber et al, 2018), and perpetration by black men (Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a recent systematic review focused on the family, Supol et al. (2020) found significant negative direct effects for exposure to family violence on adolescent achievement. Other important factors included the family's socioeconomic status, timing of the exposure, and type of violence.…”
Section: Sources Of Vulnerability: Studies Examining the Relations Be...mentioning
confidence: 99%
“…Factors related to violence are conceptualized and measured in various ways; some definitions are more interpersonal (e.g., physical abuse), while others as more intrapersonal (e.g., witnessing violence). For example, in a recent systematic review focused on the family, Supol et al (2020) found significant negative direct effects for exposure to family violence on adolescent achievement. Other important factors included the family's socioeconomic status, timing of the exposure, and type of violence.…”
Section: Reading and Violencementioning
confidence: 99%
“…D. Li et al, 2021;X. Li et al, 2022;Supol et al, 2021) demostrando que ser testigo o víctima dentro del seno familiar predicen la perpetración de agresión; si bien, los estudios son importantes, no son del todo concluyentes, debido a que no han medido los niveles de violencia o evaluada la correlación con el comportamiento académico reactivo, para ello desarrollar una revisión permite una comprensión más profunda sobre las variables en cuestión.…”
Section: Introductionunclassified